2003
DOI: 10.1128/iai.71.7.3954-3959.2003
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Germination of Bacillus anthracis Endospores Requires the gerH Operon

Abstract: The gerHABC operon of Bacillus anthracis, encoding a gerA-like family member of germinant sensors, was shown to be required for endospore germination in the presence of macrophages and in macrophage-conditioned media. The loss of the germination phenotype in macrophage cultures of B. anthracis gerH-null endospores was restored by complementation in trans with a wild-type copy of gerH expressed under the control of its own promoter. Using endospores from both the parental strain B. anthracis Sterne and an isoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
(69 reference statements)
2
42
0
Order By: Relevance
“…Therefore, we next asked whether BA spores, like LPS, could directly induce IL-1b mRNA and caspase-1 activity that processed pro-IL-1b gene product to the mature cytokine. To ensure that we were examining the initial interaction between macrophages and BA spores rather than vegetative bacilli, we used a congenic mutant of the Sterne 34F2 strain, DgerH, that germinates poorly within macrophages [14,16]. Thus, during macrophage cell culture there is limited expression of either LT or edema toxin (ET).…”
Section: Ba Spore-induced Il-1b Requires Myd88 and Caspase-1 Activationmentioning
confidence: 99%
“…Therefore, we next asked whether BA spores, like LPS, could directly induce IL-1b mRNA and caspase-1 activity that processed pro-IL-1b gene product to the mature cytokine. To ensure that we were examining the initial interaction between macrophages and BA spores rather than vegetative bacilli, we used a congenic mutant of the Sterne 34F2 strain, DgerH, that germinates poorly within macrophages [14,16]. Thus, during macrophage cell culture there is limited expression of either LT or edema toxin (ET).…”
Section: Ba Spore-induced Il-1b Requires Myd88 and Caspase-1 Activationmentioning
confidence: 99%
“…Realtime PCR allowed an evaluation of cytokine mRNA 1 h after addition of spores to M. Second, we used the ⌬gerH mutant of Sterne 34F2, which germinates poorly in the presence of M (43,44). We measured levels of IL-1␤, TNF-␣, IFN-␤, RANTES, and IL-6 because of their importance in stimulating different components of the immune response, such as phagocytes (TNF-␣, IL-1␤), B cells, and antibody formation (IL-6).…”
Section: Bmentioning
confidence: 99%
“…First, we used the germination-proficient B. anthracis Sterne strain 34F2 (pXO1 ϩ pXO2 Ϫ ) and examined the spore M interaction at 1 h, prior to the spore germination and cytokine production, by employing quantitative PCR to study cytokine gene expression. Second, we measured cytokine protein responses by M by using the congenic germination-deficient ⌬gerH (gerH-null) strain spores (43,44). The tri-cistronic gerHABC operon encodes germinant sensors in the presence of M and M-conditioned media and is required for endospore germination within the M environment (43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This did not reveal any GerT function but demonstrated that GerN is important in any circumstances where the GerI receptor is implicated in germination. In B. anthracis, the GerH germinant receptor has been implicated in virulence (26). Apart from sequence differences in the long repeat region near the N termini of GerHA and GerIA, the GerH proteins are almost identical in amino acid sequence to the GerI proteins of B. cereus ATCC 10876.…”
Section: Discussionmentioning
confidence: 87%